2016
DOI: 10.1177/2054270416632705
|View full text |Cite
|
Sign up to set email alerts
|

The association between trainee demographic factors and self-reported experience: Analysis of General Medical Council National Training Survey 2014 and 2015 data

Dipender Gill

Abstract: ObjectivesTo investigate whether demographic factors are associated with self-reported experience amongst medical trainees in the UK.DesignRetrospective analysis of survey data.SettingGeneral Medical Council (UK) National Training Survey data for 2014 and 2015.ParticipantsA total of 105,549 responses were provided from 68,551 participants when no data were removed. After removing data to preserve participant anonymity, there were 64,278 participants providing 99,076 responses.Main outcome measuresConsidered tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…33 The perception that bias can affect learning is reflected by national surveys reporting that newly qualified BME UKGs were less likely to agree ‘the NHS is a good equal opportunities employer for doctors from ethnic minorities’34 and were less satisfied with their training35 although IMGs were more satisfied than UKGs 35. It may be that IMGs have different expectations—one IMG in our study expected to be discriminated against, feeling it was natural to prefer one's own (black IMG ST1–3 medicine).…”
Section: Discussionmentioning
confidence: 99%
“…33 The perception that bias can affect learning is reflected by national surveys reporting that newly qualified BME UKGs were less likely to agree ‘the NHS is a good equal opportunities employer for doctors from ethnic minorities’34 and were less satisfied with their training35 although IMGs were more satisfied than UKGs 35. It may be that IMGs have different expectations—one IMG in our study expected to be discriminated against, feeling it was natural to prefer one's own (black IMG ST1–3 medicine).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 22 studies found moderate ( d = 0.42) effects whereby ethnically non-white UK graduates underperformed relative to white UK graduates in assessments at both undergraduate and postgraduate levels. Nor is it merely an assessment issue – questionnaires evaluating the postgraduate working experience find ethnically non-white trainees experience lower levels of satisfaction [ 5 ]. In relation to sex, there is evidence that men and women prefer different types of assessment and in at least one case – true/false MCQs (Multiple Choice Questions) where candidates are penalised for incorrect answers – the format of the assessment can produce significant sex differences [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is an assertion that the number of cases undertaken by trainees has fallen over time. This has been attributed to (among other reasons) organisational and political changes such as the European Working Time Directive . England reported that trainees undertook around 1000 cases per year in 1990, but by 1999, this figure had dropped to 500 with this downward trend persisting .…”
Section: Discussionmentioning
confidence: 99%
“…Minimum competencies are specified in the training curriculum that is maintained by the RCoA . However, experience accrued during the course of postgraduate specialty training is thought to vary across geographical regions . In recent years, training in anaesthesia has undergone significant change.…”
Section: Introductionmentioning
confidence: 99%